Orobanche flava (Orobanchaceae) in Poland: current distribution, taxonomy, hosts and plant communities - Piwowarczyk, Renata (Biodiversity: Research and Conservation, 2015)
Orobanche flava is a species of Central European mountain ranges, mainly the Alps and Carpathian Mts. The paper presents the current distribution of O. flava in Poland based on a critical revision of herbarium and literature data as well as results of field investigations conducted between 1999 and 2014. The distribution of species is centered in southern Poland, mainly in the Carpathian Mts., and, sporadically, in the Sudeten Mts. The distribution of O. flava in Poland is mapped. The taxonomy, biology, and ecology are also discussed.